29 Eccentric Vs. Concentric Loading Of The Plantarflexors – A Biomechanical Investigation. (5th September 2014) - Debenham, James; Wellisch, Matthew; Hamer, Peter; Hopper, Luke
Abstract : Introduction: Achilles tendinopathy is a common musculoskeletal condition driven in part by alterations in muscle performance. 1 Whilst eccentric loading has demonstrated clinical efficacy, and superiority to concentric loading, the underlying mechanisms behind this benefit are largely unknown. 2 One potential mechanism is a shift of angle to peak torque (AtPT) of the plantarflexors to a lengthened position as has been demonstrated elsewhere. 3 This study compared the influence of eccentric vs. concentric loading on the AtPT and peak torque (PT) of the plantarflexors. Methods: Double-blind randomised control design. 30 healthy volunteers (23 ± 4 years) were randomly allocated to eccentric (ECC) or concentric (CON) groups. Baseline measures of AtPT and PT were obtained using isokinetic dynamometry. The exercise intervention reflected that described by Alfredson [1998], with the ECC and CON groups performing eccentric or concentric contractions only respectively; load was progressively increased over a 10-week intervention period. Repeated measures of AtPT and PT were obtained and statistically analysed. Results: AtPT was significantly increased (p < 0.001) in the ECC group (pre, 25.6º ±. 6 to post, 28.7º ±. 7) but not in the CON group (p = 0.498). Furthermore, post-exercise comparison of the 2 groups revealed a significant difference in AtPT (p < 0.001) (Figure 1 ). There was no significant difference in PT for the ECC (p = 0.814) or CON groups (p = 0.216) (Figure 2 ). Discussion: These findings demonstrate that a clinically-derived eccentric loading protocol results in a shift in AtPT towards a longer length (i.e. further towards dorsiflexion), whilst not altering peak torque. This is in contrast to a concentric loading protocol that did not induce such changes. These findings offer a novel explanation regarding the mechanism of efficacy for eccentric loading, consistent with a mechanical pathoaetiological model of stretch-shortening cycle failure. References: Fu, et al . Sports Med Arthrosc Rehabil Ther Technol. 2010;2:30 Crill, et al . Foot Ankle Spec. 2014 Epub 20 July 2014, DOI: 10.1177/1938640014539812 Brocket, et al . Med Sci Sports Exerc. 2001;33:783–790 Alfredson et al . Am J Sports Med. 1998;26:360–366